On convergence theorems for homeomorphisms of Sobolev class - Ryazanov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We prove a new convergence theorem for homeomorphisms of Sobolev class with a locally summable upper bound of deformations. This theorem allows us to generalize the known Strebel and Bers-Boyarskii convergence theorems.